2003
DOI: 10.1177/107179190301000205
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence Process: Development of a Stage Model For Goal-Directed Behavior

Abstract: This paper provides a theoretical framework for persistence as a process in goal-directed behavior. The theoretical foundation builds on the recent formulation of an instability function in planned behavior and develops a stage model of persistence. Stages discussed in this paper include those related to decision-making, implementation and evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…It can even increase if every action is always updated. In accordance with several explanations of the results of previous studies, it is confirmed by Meier & Albrecht (2003) that there are three stages in the persistence process, namely; decision objectives, implementation, and evaluation.…”
Section: Resultssupporting
confidence: 88%
“…It can even increase if every action is always updated. In accordance with several explanations of the results of previous studies, it is confirmed by Meier & Albrecht (2003) that there are three stages in the persistence process, namely; decision objectives, implementation, and evaluation.…”
Section: Resultssupporting
confidence: 88%
“…Further investigation of the proposed framework for perseverance is required. Recognising that perseverance is a dynamic behaviour [ 13 , 14 ], it will be critical to next use this framework to explore stroke survivors’ perspectives on perseverance in the context of stroke rehabilitation, the factors that mediate perservence, and the relative contribution of each mediating factor to their ability to persevere. Taken together, such information will be critical to informing the development of a stroke specific measure of perseverance, and allow us to design and implement strategies to enhance perseverance.…”
Section: Discussionmentioning
confidence: 99%
“…Whether due to the tedium of the task at hand or the pull of the many more immediate gratifications that abound in our environments, success often requires persisting through some “unpleasure” (Duckworth, Kirby, Tsukayama, Berstein, & Ericsson, ; Ericsson, ; Freud, 1916–1917). The ability to push through when confronted with these obstacles has been linked to intelligence, school achievement, and work success (Meier & Albrecht, ). Thus, understanding how perseverance manifests in the face of environmental temptations is important.…”
Section: Present Studymentioning
confidence: 99%